Software Readability Metrics: A Systematic Literature Review (2020)
Software quality is an aspect directly linked to future maintenance costs, and is generally quantified by means of quality metrics of the software products. One of the main aspects to evaluate software quality is its maintainability, since it has a high impact on the total costs of software projects. In particular, it is estimated that 70% of the maintenance time is dedicated to understand the code, so it is important to be able to measure the readability of a source code fragment properly. Readability is defined as the ease with which a person can read and understand a piece of code written by another person, this feature is crucial to facilitate the understanding of the code during software maintenance tasks. In this sense, it is necessary to be able to measure the readability of the source code. Therefore, over the past few years, researchers in the area have proposed multiple metrics to measure the readability of source code. However, it remains a challenge to be able to accurately assess the readability of source code in a widely accepted way. Therefore, it is essential to give continuity to this type of research and, for this, it is necessary to know the most recent advances. This paper presents a synthesis and analysis of code readability metrics, through a systematic review of literature, showing a compilation of the characteristics and methods used for their measurement. Results of this work will be useful for researchers in the area to propose new source code readability metrics.